MODEL WELENRENGNGE: PEMBENTUKAN KARAKTER “MARITIM” MAHASISWA DI MAKASSAR - A B.Takko Bandung Bandung (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2019)
As a way to strengthen the MARITIM character (MARITIM as an abbreviation of Manusiawi (Humane), Arif (Wise), Religious, Innovative, Tough, Integrity, Mandiri (Independent)) of students, a training was conducted. The method employed was Welenrengnge Method. This method included thorough reading of the training materials, in-depth discussions, fieldwork training, tutorial, and discussions involving question-and-answer sessions regarding the MARITIM character. Each participant would make a discussion report. A fieldwork was conducted to apply games to implement MARITIM character. Tutorial was conducted for consultation and to enhance the understanding and application of MARITIM character. The results of the training showed that students were aware of the importance of the training since they improved their knowledge, perspectives and improving creativity and innovation through games. The practice through games could build wisdom, independence toughness and humanity in religious situation.   Keywords: Student, Training, Welenrengnge, MARITIM Character